1999
DOI: 10.1111/j.1478-3231.1999.tb00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment of chronic hepatitis C with ursodeoxycholic acid: influence of HCV genotypes and severity of liver disease

Abstract: Long-term UDCA treatment is well tolerated in patients with HCV-associated chronic liver disease. The effect appears to be greater in cirrhotics than in patients with chronic hepatitis but is independent of HCV genotypes. Thus, long-term UDCA treatment, despite the absence of an anti-viral effect, seems beneficial in reducing disease activity in patients with chronic hepatitis or cirrhosis who are unsuitable for IFN therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 59 publications
0
15
1
Order By: Relevance
“…These results suggested that 900 mg of UDCA can improve liver function tests in patients with chronic hepatitis C who have already received 600 mg of UDCA. In this study, the frequency of adverse events was lower than those in previous reports [15][16][17][18] . A possible reason for this is that patients enrolled in this study were not naïve to UDCA and may have quickly gotten used to the administration of UDCA.…”
Section: Discussioncontrasting
confidence: 86%
“…These results suggested that 900 mg of UDCA can improve liver function tests in patients with chronic hepatitis C who have already received 600 mg of UDCA. In this study, the frequency of adverse events was lower than those in previous reports [15][16][17][18] . A possible reason for this is that patients enrolled in this study were not naïve to UDCA and may have quickly gotten used to the administration of UDCA.…”
Section: Discussioncontrasting
confidence: 86%
“…For the treatment of HCV-infected and relapsed patients, interferon is used separately or in combination with ribavirin or ursodeoxycholic acid [Lirussi et al, 1999;Salmeron et al, 1999]. However, interferon is inconvenient to use and can cause complications.…”
Section: Discussionmentioning
confidence: 99%
“…(Evidence level C.) Comment: Ursodeoxycholic acid (UDCA) stabilizes serum ALT levels in HCV-related liver cirrhosis [65], and glycyrrhizin injection is useful for the prevention of disease progression [66]. However, their effects on liver fibrosis have not been confirmed.…”
Section: Antifibrotic Therapymentioning
confidence: 99%